Social services Interventions and the Mental Health and Mortality of care leavers: a population based data linkage study in Northern Ireland and Finland - Maguire, Aideen; Kouvonen, Anne; O'Reilly, Dermot; Remes, Hanna; Pitkänen, Joonas; Martikainen, Pekka (International Journal of Population Data Science, 2019)
Background Research has highlighted the poor mental health of looked after children compared to those never in care. However, little is known on what becomes of these children and their mental health trajectories after they leave the care of social services. In addition, previous studies are limited in their ability to differentiate between type of social care intervention received; kinship care, foster care or residential care. Aim To utilise nationwide social services data from two countries (Northern Ireland (NI) and Finland), with similar populations but different intervention policies, linked to a range of demographic and health datasets to examine the mental health outcomes of young adults in the years following leaving care. Methods Data from both countries on children born 1991-2000 were linked to social services data, hospital admissions, prescribed medication data and death records. Mental health outcomes were defined after the age of 18years (when statutory care provision ends) examined by care intervention and included admissions to psychiatric hospital, for self-harm and death by suicide. Results The gender split in care in Finland is reflective of the population but more males are in care in NI. Initial results from Finnish data suggest those exposed to care in childhood have an increased risk of self-harm, psychiatric hospital admission and suicide after the age of 18years compared to those never in care. After adjusting for gender, age of entry to care and deprivation at birth those exposed to any care intervention had 3 times the risk of suicide (HR=3.06, 95% CI 1.18,7.98). Risk increased with duration in care but was equivalent across care intervention types. Analysis on the NI data is underway. Conclusion Full results will be available December 2019 and will explore which care pathways are most associated with poor mental health outcomes informing discussion around intervention opportunities and policy.